Meningkatkan Pembelajaran Agama Hindu Siswa Kelas X SMA Negeri 1 Tabanan Dengan Menggunakan Metode Self Directed Learning Berbasis ICT - Giantara, I Putu (Yayasan Pendidikan Internasional Bengkulu, 2024)
This study aims to improve students' abilities in learning Hinduism using the ICT-based Self Directed Learning method. The type of research used is the Classroom Action Research (CAR) type by describing qualitative and quantitative descriptive. The subjects of this study were all 45 Hindu students of class X 2 SMA Negeri 1 Tabanan consisting of 19 males and 24 females. The objects of this study are divided into two, namely those that show the process and those that show the results. The object that shows the process is the use of the ICT-based Self Directed Learning method, while the object that shows the results is the increase in students' abilities in learning Hinduism. The research methods used are: (1) Type of Research, (2) Subject and object of research, (3) Research guide, (4) Techniques and methods of collecting data, (5) Test results. The results of this study indicate that using the Self Directed Learning method in learning Hinduism can improve student learning outcomes. In addition, students' responses regarding the use of ICT-based Self Directed Learning methods in learning Hinduism can be said to be good, because using ICT-based Self Directed Learning methods can create a sense of enthusiasm in students to learn and help students understand the material.